کلام ِاقبال میں قومی یکجہتی : عصر حاضر کے تناظر میں: National Unity in Iqbal’s Poetry: In the Contemporary Context - Muhammad Kashif; Dr. Muhammad Asghar Sial (Tashkeel e Jadeed, 2025)
In the contemporary context, the significance of Allama Muhammad Iqbal's (1877–1938) thought in relation to the renaissance of Islam cannot be overstated. Iqbal was deeply rooted in both traditional Islamic sciences and modern disciplines, which enabled him to serve as a pioneering voice for the reinterpretation of Islam in accordance with the evolving demands of the modern Muslim world. His philosophical lectures, visionary poetry, and scholarly correspondence remain invaluable sources of wisdom and guidance. With remarkable foresight, Iqbal anticipated the transformations of the modern era and the resulting socio-political and intellectual challenges. Emphasizing a life aligned with the true spirit of Islam, he advocated for a spiritually meaningful worldview capable of revitalizing not only the Muslim Ummah but all of humanity. At a time when Muslim societies were plagued by intellectual decline and disillusionment with Islamic ideals, Iqbal’s message emerged as a beacon of hope. This paper critically examines Iqbal’s poetry, letters, and essays to explore his vision of national cohesion and its applicability in the contemporary world. His ideas continue to offer actionable insights for collective and national revival even today.